Study of serum lipid profile in type 2 diabetes mellitus patients and its association with diabetic nephropathy - Kolhar, Ullasini; P., Priyanka (International Journal of Advances in Medicine, 2017)
Background: Dyslipidaemia is highly prevalent in type 2 Diabetes mellitus patients. The role of dyslipidaemia in macrovascular complications of Diabetes have been extensively studied but its role in microvascular complications namely nephropathy is still unclear. The present study was undertaken to study the prevalence and pattern of dyslipidaemia and its association with Diabetic nephropathy (DN) in patients with type 2 DM. Methods: 100 patients with type 2 DM attending OPD or admitted, over a period of 1 year were studied. Detailed history was taken and clinical examination was done. Serum lipid profile was studied in all patients and its association with DN was assessed. Results: The prevalence of dyslipidaemia in DM patients in our study was 90% and there was no statistically significant difference in the prevalence among males and females. Poorly controlled diabetics had high prevalence of dyslipidaemia as compared to well controlled diabetics. The prevalence of Diabetic nephropathy in our study was 41%. There was significant association of DN with high Total Cholesterol, high Low-density lipoprotein (LDL-C) and high Triglycerides. There was no significant association of DN with High density lipoprotein (HDL-C). Conclusions: Present study highlights the magnitude of dyslipidaemia in type2 DM patients and that there is a significant association of DN with lipid parameters. Hence patients should be managed with life style modifications with or without lipid lowering agents to achieve target lipid values along with adequate glycemic control to prevent or delay the appearance and progression of DN.